Methods in Quaternary Ecology #8. Non-marine Molluscs - Miller, Barry; Bajc, Andrew (Geoscience Canada)

(untitled) (The Geological Association of Canada, 1989)
Summary Molluscs are among the most ubiquitous fossils found in Quaternary non-marinesediments. They are found in a wide variety of deposits including: loess, cave, sinkhole and fissure deposits; fluvial, lacustrine, glaciolacustrine and paludal sediments; and spring-fed travertine accumulations. In spite of problems associated with identification of some species from shell morphology alone and a general inadequacy in our understanding of the factors controlling modern species distribution, Quaternary studies of non-marine molluscs have resulted in some significant contributions. In North America fossil molluscs have been used to: (1) reconstruct former stream confluences; (2) provide a basis for biostratigraphic zonation of sedimentary sequences in the Lake Michigan, Superior and Huronbasins; and (3) reconstruct local habitat and climatic conditions. Isotopic data obtainedf rom the analysis of mollus can shell has provided information about the environment in which the molluscs lived. Amino acid stud-ies of the shell protein have provided infor-mation about the age of fossil assemblagesand a method for estimating post depositional effective temperature histories of fossil sites. One of the basic problems in Quaternary biogeography concerns the timing, the nature, and the magnitude of biotic changes that accompanied glacial advances and retreats. The ubiquity of non-marine molluscsin Quaternary sediments provides an excellent opportunity to study effects of both short and long scale climatic fluctuations on at least one important part of the non-marinebiota, the molluscs.